Nano/Microrobots Meet Electrochemistry. (13th February 2017) - Moo, James Guo Sheng; Mayorga‐Martinez, Carmen C.; Wang, Hong; Khezri, Bahareh; Teo, Wei Zhe; Pumera, Martin
Abstract : Artificial autonomous self‐propelled nano and microrobots are an important part of contemporary technology. They are typically self‐powered, taking chemical energy from their environment and converting it to motion. They can move in complex environments and channels, deliver cargo, perform nanosurgery, act as chemotaxis and perform sense‐and‐act actions. The electrochemistry is closely interwoven within this field. In the case of self‐electrophoretically driven nano/microrobots, electrochemical mechanism has been the basis of power, which translates chemical energy to motion. Electrochemistry is also a major tool for the fabrication of these micro and nanodevices. Electrochemistry and electric fields can be used for the directing of nanorobots and for detection of their positions. Ultimately, nano and microrobots can dramatically improve performances of electrochemical sensors and biosensors, as well as of the energy generating devices. Here, all aspects in the fundamentals and applications of electrochemistry in the realm of nano‐ and microrobots are reviewed. Abstract : The nexus between electrochemistry and nano/microrobots is closely interwoven . In this confluence, fabrication, powering, control and applications of these self‐propelled devices are illustrated. Understanding these fundamentals will push new frontiers for the locomotion of nano/microrobots.